Oral Mucocele Case Series: A Review of Surgical Options and Clinical Findings - Manisha Chaudhary; Akash Kumar Giri (Journal of Primary Care Dentistry and Oral Health)
Mucocele, a benign lesion on the lower lip that is often caused by lip-biting habit and local trauma, is a frequent oral lesion in children. Anxiety is a common psychological condition that drives lip-biting behavior. Although mucoceles may not cause pain, individuals may find them uncomfortable when speaking and eating. Even though they can affect anyone, mucoceles are more common in younger people. Although there are several possible causes of oral mucoceles, surgery is the most recommended course of action due to its ease of use, child-friendliness, and high rate of success. To break the behavior of lip-biting, parents and kids must get awareness education.